Screening for diabetes prevention with diabetes risk scores – A balancing act - Lee, Crystal; Versace, V.; Malo, J.; Shaw, J.; Dunbar, J.; Colagiuri, S. (Elsevier Ireland Ltd, 2018)
Aims: To compare the diabetes prevention impact and cost of several screening scenarios for diabetes prevention programs with the scenario which included an oral glucose tolerance test (OGTT). Methods: We included 4864 participants of the Australian Diabetes, Obesity and Lifestyle study who were aged =40 years, did not have known diabetes at baseline, and attended the five year follow-up. The proportions of participants eligible or ineligible for diabetes prevention program were estimated for each scenario. The costs of screening and diabetes prevention programs were also estimated. Results Screening with OGTT alone identified 21% of participants as eligible for diabetes prevention. While 3.1% of the cohort were identified as high risk and developed diabetes after five years, 1.0% of the cohort were identified as low risk and developed diabetes. The population prevention potential (i.e. sensitivity) for OGTT alone was 76.5%. Screening all Australian adults aged =40 years in 2015 by OGTT would have cost a total of AU$2025 million (AU$1031 million on screening and AU$994 million on prevention programs). The total costs of screening and prevention were substantially lower when AUSDRISK was used alone or in combination with a blood test. However, the population prevention potentials were also lower (ranged from 20.1% to 50.7%). Conclusions: A blood test post non-invasive risk assessment is a worthwhile step in the process of enrolling participants in a diabetes prevention program. Nevertheless, there will be ineligible individuals who proceed to diabetes.